Decentralization and local public services in Ghana: Do geography and ethnic diversity matter? - Akramov, Kamiljon T.; Asante, Felix Ankomah (International Food Policy Research Institute, 2008)
This paper explores disparities in local public service provision between decentralized districts in Ghana using district and household level data. The results show that districts' geography plays a major role in shaping disparities in access to local public services in Ghana. The findings also suggest that ethnic diversity has significant negative impact on access to local public services, including drinking water. This negative impact is significantly higher in rural areas. However, the negative impact of ethnic diversity in access to local public services, including drinking water, decreases as average literacy level increases. The paper relates these results to the literature and discusses policy implications.